The experience of offshore fish farming in France - Pomélie C. de la; Paquotte P. (Mediterranean offshore mariculture, 2000)
A natural endowment of three different coastlines, of numerous rivers coming from different climatic regions has enabled France to develop one of the first European aquaculture sectors. A development based on a wide range of species and techniques. Intensive marine fish farming has only been developing during the last decade, due to the lack of reliable technology for species suitable for the French climate. Techniques of production are very diverse. Earth ponds and raceways (25 per cent of the marine fish farms) accounts for 40 per cent of the production. By contrast, there are many small farms using different types of floating cages in semi-offshore conditions for seabass and seabream. French aquaculture has given up projects involving heavy and costly offshore infrastructures inspired from the oil industry or resulting from the reconversion of cargo vessels, but has not yet taken up all the possibilities given by the experience gained in offshore salmon farming.
Advanced Course of the CIHEAM Network on Technology of Aquaculture in the Mediterranean on 'Mediterranean Offshore Mariculture', 1997/10/20-24, Zaragoza (Spain)